Transformation the next step for the no-limit person - Dyer, Wayne, Dr. ([New York] : Nightingale-Conant Corporation, 1995)
In Transformation, you will learn how to use the powerful connection between thoughts and reality to break from the roles that control your life. With Wayne Dyer, it's not a New Age mystery, but a clear path from negative to positive thinking that will lead you to become the person you were truly meant to be.
Title from container
Keywords: Self-actualization (Psychology).